2019
DOI: 10.1177/1533033819864311
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CD133 Overcomes Cisplatin Resistance Through Inhibiting PI3K/AKT/mTOR Signaling Pathway and Autophagy in CD133-Positive Gastric Cancer Cells

Abstract: Cisplatin is widely used as the standard gastric cancer treatment, but the relapse and metastasis are common as intrinsic or acquired drug resistance. CD133 has been widely known to be associated with chemoresistance in various cancer cells. In this study, we focused on investigating the function and mechanism of CD133 underlying cisplatin resistance in gastric cancer cell line KATO-III. We detected CD133 expression by using quantitative real-time polymerase chain reaction and Western blot and found that expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…28,29 The increased expression of the phosphorylate-type AKT, that is the activation of AKT signaling, is observed in the osteosarcoma cells. 30 It has been reported that the AKT-related signaling pathway mediates drug-resistance in various cancers, such as in gastric cancer 31 and in breast cancer, 32 as well as in osteosarcoma cells. 33 In this research, we found that both PMA-differentiated THP1 and macrophagederived exosomes signicantly increased the expression of phosphorylated AKT, and that the AKT inhibitor MK2206 reversed the effect of the macrophage-derived exosomes, indicating that the macrophage-derived exosomes activated the AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 The increased expression of the phosphorylate-type AKT, that is the activation of AKT signaling, is observed in the osteosarcoma cells. 30 It has been reported that the AKT-related signaling pathway mediates drug-resistance in various cancers, such as in gastric cancer 31 and in breast cancer, 32 as well as in osteosarcoma cells. 33 In this research, we found that both PMA-differentiated THP1 and macrophagederived exosomes signicantly increased the expression of phosphorylated AKT, and that the AKT inhibitor MK2206 reversed the effect of the macrophage-derived exosomes, indicating that the macrophage-derived exosomes activated the AKT signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the mechanism through which STIP1 acts on the JAK2/STAT3 signaling pathway also requires further investigation. STIP1, HSP70, and HSP90 are all highly expressed and interact in colon cancer tissue,25 while HSP90 acts on Akt to promote cell growth and inhibit apoptosis 26. STIP1 can also interact with gene promoters; for example, STIP1 can accelerate SMAD protein binding to the ID3 promoter, thereby enhancing ovarian cancer cell proliferation and growth 27.…”
Section: Discussionmentioning
confidence: 99%
“…Specific ABCG2 inhibitor Pantoprazole or ABC transporter inhibitor Verapamil can reduce tumor resistance to platinum [16]. It has been reported that CD133 mediates cisplatin resistance that can overcome by inhibition of CD133 [17].…”
Section: Potential Cscs Markers and Therapy Resistancementioning
confidence: 99%